Influencer Marketing Unveiled: Navigating the Dynamics of Social Media Impact, and a Comprehensive Bibliometric Analysis - Bhandari, Gyani (Janaprakash Journal of Multidisciplinary Research, 2023)
This article explores the intricate landscape of influencer marketing within the realm of social media, with a specific focus on the evolving role of influencers, and their significant impact on consumer behavior. The study employs a rigorous bibliometric analysis, utilizing the Dimensions Digital Science database, to uncover key research trends, influential works, and collaborative networks in the influencer marketing domain. The methodology ensures transparency and reproducibility in data collection, leading to a carefully curated dataset. The literature review sheds light on the complexities of influencer-brand collaborations, emphasizing the need for authenticity. Through real-world examples, the article highlights the potential pitfalls in influencer marketing and the importance of congruence between influencers and brands for successful outcomes. The findings contribute to a collective understanding of influencer marketing, providing valuable insights for marketers, scholars, and industry professionals.